The Roles of Health Literacy and Physician-Patient Relationship in Self-Reported Health Outcomes Within a Diverse Sample of Persons Living with HIV. (30th August 2019) - Santana, E; Gonzalez, J; Byrd, D; Rivera Mindt, M
Abstract: Objective: Barriers like poor health literacy and patient-provider communication add to health disparities in diverse populations. Perceived autonomy has been shown to improve patients' health satisfaction and knowledge of their illness. However, no studies have examined these issues in HIV patients. This study examined the roles of health literacy and physician-patient relationship in health outcomes (e.g., mental health and emotional/physical functioning) in persons living with HIV (PLWH). Participants and Method: This cross-sectional study included 91 PLWH (74% Latinx and 26% non-Latinx White; 68% Male) who completed the Test of Functional Health Literacy in Adults (TOFHLA), Physician–Patient Relationship Scale (PPRS), and Medical Outcomes Study-HIV Health Survey (MOS). The study variables included: TOFHLA total score, PPRS Part Decision- Making (PDM) and Trust subscales, and MOS Mental Health and Health Transition subscales. Results: A linear regression showed that our model (ethnicity, TOFHLA, PPRS PDM and Trust) predicted MOS HT (R 2 = .14, p < 0.05), such that Latinx ethnicity (β = .30) and better TOFHLA scores (β = -.22) predicted better MOS HT scores (ps < .05). Another regression showed that our model predicted MOS MH (R 2 = 0.07, p = <.01), such that greater PPRS PDM scores predicted better MOS MH scores (β = .27, p = <.01). Conclusions: Ethnicity and better health literacy were related to improved emotional/physical functioning over a 4-week period and greater shared decision-making was related to better overall mental health. These findings highlight the importance of identifying sociocultural factors and interpersonal processes of care to inform culturally-tailored interventions that can result in enhanced and effective treatment for PLWH patients and in improved physical and mental health outcomes.